Imaging the microanatomy of astrocyte–T-cell interactions in immune-mediated inflammation - Barcia, Carlos; Mitxitorena, Izaskun; Carrillo-de Sauvage, María A.; Gallego, José M.; Barcia, Carlos; Perez-Valles, Ana (Frontiers in Cellular Neuroscience, 2013)
The role of astrocytes in the immune-mediated inflammatory response in the brain is more prominent than previously thought. Astrocytes become reactive in response to neuro-inflammatory stimuli through multiple pathways, contributing significantly to the machinery that modifies the parenchymal environment. In particular, astrocytic signaling induces the establishment of critical relationships with infiltrating blood cells, such as lymphocytes, which is a fundamental process for an effective immune response. The interaction between astrocytes and T-cells involves complex modifications to both cell types, which undergo micro-anatomical changes and the redistribution of their binding and secretory domains. These modifications are critical for different immunological responses, such as for the effectiveness of the T-cell response, for the specific infiltration of these cells and their homing in the brain parenchyma, and for their correct apposition with antigen-presenting cells to form immunological synapses. In this article, we review the current knowledge of the interactions between T-cells and astrocytes in the context of immune-mediated inflammation in the brain, based on the micro-anatomical imaging of these appositions by high-resolution confocal microscopy and three-dimensional rendering. The study of these dynamic interactions using detailed technical approaches contributes to understanding the function of astrocytes in inflammatory responses and paves the way for new therapeutic strategies.